CAR immunotherapy in autoimmune diseases: promises and challenges - Yu, Jingjing; Yang, Yiming; Gu, Zhanjing; Shi, Min; La Cava, Antonio; Liu, Aijing (Frontiers in Immunology, 2024)
In recent years, the use of chimeric antigen receptor (CAR)-T cells has emerged as a promising immunotherapy in multiple diseases. CAR-T cells are T cells genetically modified to express a surface receptor, known as CAR, for the targeting of cognate antigens on specific cells. The effectiveness of CAR-T cell therapy in hematologic malignancies including leukemia, myeloma, and non-Hodgkin's lymphoma has led to consider it as a potential avenue of treatment for autoimmune diseases. However, broadening the use of CAR-T cell therapy to a large spectrum of autoimmune conditions is challenging particularly because of the possible development of side effects including cytokine release syndrome and neurotoxicity. The design of CAR therapy that include additional immune cells such as double-negative T cells, γδ T cells, T regulatory cells and natural killer cells has shown promising results in preclinical studies and clinical trials in oncology, suggesting a similar potential utility in the treatment of autoimmune diseases. This review examines the mechanisms, efficacy, and safety of CAR approaches with a focus on their use in autoimmune diseases including systemic lupus erythematosus, sjogren's syndrome, systemic sclerosis, multiple sclerosis, myasthenia gravis, lupus nephritis and other autoimmune diseases. Advantages and disadvantages as comparison to CAR-T cell therapy will also be discussed.